1899 N.D. Rev. Codes 1533-34, Penal Code, ch. 72, § 7, pt. 5. - (:unkn) unknown (My University, 1899)
Every person who either . . . at any time kills or shoots any wild duck, goose, crane or brant with a swivel gun or other guns except such as is commonly shot from the shoulder, or in hunting such birds makes use of any artificial light or battery . . . Is guilty of a misdemeanor, and upon conviction thereof before any justice of the peace of the county, is punishable by a fine of not exceeding ten dollars for each of the birds mentioned in subdivisions 1, 2, 3, or 4 of this section, so shot or killed or nest or eggs so destroyed[.]
Keywords: HUNTING REGULATION